Extreme Temperature Events (ETEs) in South Africa: a review. Issue 1 (2nd January 2022) - Van Der Walt, Adriaan J.; Fitchett, Jennifer M.
ABSTRACT: Extreme Temperature Events (ETEs), including heatwaves, warm spells, cold waves and cold spells, have disastrous impacts on human health and ecosystems. The frequency, intensity, and duration of ETEs is projected to increase due to climate change. However, very little research has been done on ETEs in South Africa, and only a few attempts have been made to identify and examine trends. Currently, ten known publications have examined ETEs across South Africa, the majority of which use the South African Weather Service (SAWS) climate database as the primary source. The general findings indicate that the incidence and duration of extreme warm temperatures are increasing, while cold extremes are decreasing. However, inconstancies exist in the indices used to identify ETEs, selection of meteorological stations, study period, and statistical methods used to examine trends. We review the methodological approaches to define ETEs, the extreme temperature indices adopted, the selection of meteorological stations, study periods, data quality and homogeneity, statistical trend analysis, and results. From these, we propose an approximate number of stations to adequately portray temperature variability on a national and regional level. Finally, we reflect on projections of ETEs under current climate change conditions, and the implications of cold and warm ETEs in a South African context.